(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
Ten in the morning is not the most usual time for a press view to open, nor is the requirement to show ID and Vaccination Pass, but at the Palazzo Cipolla (lit. “Onion Palace”) on the Corso del Rinascimento in the centre of Rome, this was the the routine to see an intriguing show of work by David Quayola, an Italian digital artist, long resident in London, but here displaying a variety of pieces made over the last fourteen years. Suffice to say there was not an ice filled dustbin of Peroni bottles in sight.